2022
DOI: 10.1038/s41598-022-25757-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection and vaccine have no impact on in-vitro fertilization (IVF) outcome

Abstract: To investigate the effect of COVID-19 infection or vaccine on IVF outcome. This is a multicenter retrospective study. Data were collected from all patients treated in the ART units between September and November 2021 after the vaccination of the general population began. Medical records of all patients who had IVF/intracytoplasmic sperm injection (ICSI) were retrospectively reviewed. Patients were categorized into four groups: previously infected by COVID-19, vaccinated by COVID vaccine, previously infected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Therefore, when the new SARS-CoV-2 virus emerged and spread globally, researchers focused on the impact of infection with this virus on human reproduction and ART outcomes [5]. The effects of SARS-CoV-2 infection on the laboratory and clinical outcomes of ART have not yet been consistently documented in the literature [14,[29][30][31]. An unclear infection status, the inability to correctly measure the time between SARS-CoV-2 infection and ART treatment, and the absence of a strati cation analysis on the time of oocyte retrieval relative to SARS-CoV-2 infection could all be contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when the new SARS-CoV-2 virus emerged and spread globally, researchers focused on the impact of infection with this virus on human reproduction and ART outcomes [5]. The effects of SARS-CoV-2 infection on the laboratory and clinical outcomes of ART have not yet been consistently documented in the literature [14,[29][30][31]. An unclear infection status, the inability to correctly measure the time between SARS-CoV-2 infection and ART treatment, and the absence of a strati cation analysis on the time of oocyte retrieval relative to SARS-CoV-2 infection could all be contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Among the included studies, 12 reported the number of oocytes retrieved, comprising 536 infected versus 677 uninfected cycles. 14,15,24,[26][27][28][29]31,32,[34][35][36] The mean oocyte number was estimated to be 10.67 versus 10.61 (MD = 0.06; 95% CI: −0.75-0.88; p = .88) after meta-analysis (Figure 3A). Six studies (n = 517) provided information on the number of fertilized oocytes, 14,26,27,31,35,36 and a significant increase was noticed in the infected group (MD = 0.79; 95% CI: 0.20-1.38; p = .008) (Figure 3D).…”
Section: Meta-analysis Of Laboratory Parametersmentioning
confidence: 99%
“…14,15,24,[26][27][28][29]31,32,[34][35][36] The mean oocyte number was estimated to be 10.67 versus 10.61 (MD = 0.06; 95% CI: −0.75-0.88; p = .88) after meta-analysis (Figure 3A). Six studies (n = 517) provided information on the number of fertilized oocytes, 14,26,27,31,35,36 and a significant increase was noticed in the infected group (MD = 0.79; 95% CI: 0.20-1.38; p = .008) (Figure 3D). The pooled results of the other laboratory parameters were comparable in the number of mature oocytes (8 studies; MD = −0.29; 95% CI: −1.65-1.06; p = .67), 14,15,[26][27][28][29]31,36 oocyte maturation rate (five studies; MD = −3.20; 95% CI: −7.43-1.04; p = .14), 14,15,28,34,36 fertilization rate (five studies; MD = 1.97; 95% CI: −1.54-5.48; p = .27), 14,26,28,34,36 number of good-quality embryos (four studies; MD = −0.60; 95% CI: −2.32-1.12; p = .50), 14,24,35,36 and good-quality embryo rate (three studies; MD = −14.76; 95% CI: −33.99-4.47; p = .13) 14,…”
Section: Meta-analysis Of Laboratory Parametersmentioning
confidence: 99%
See 2 more Smart Citations